The Effectiveness of Dohsa Psycho-Rehabilitation Method on Adaptive Behavior in Children with Autism - Sadati Firoozabadi, Somayeh; Ghorbanzade , Zahra (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: Numerous studies have shown that children with autism show significant deficits in adaptive and social behavior and lack the necessary abilities to establish effective social communication with others. This study aimed to investigate the effectiveness of the Dohsa psycho-rehabilitation method (Dohsa-hou) on adaptive behavior in children with autism spectrum disorder. Materials and Methods: This study used a pre-test and post-test control group quasi-experimental design. The statistical population of the study consisted of all children with autism in Mashhad. The study sample consisted of 30 children with autism, randomly selected and aged 6 to 11 years. The experimental group received the Dohsa Psycho-Rehabilitation Method (Dohsa-Hou) treatment program. The Adaptive Behavior Scale was used as the research instrument. The treatment consisted of 12 55-minute sessions, held twice a week for each child. The data obtained from the questionnaire were analyzed using SPSS software, employing both descriptive (mean and standard deviation) and inferential (multivariate analysis of covariance) statistics. Results: The results showed that the Dohsa-hou psycho-rehabilitation method improved adaptive behavior and its components in children with autism (P<0.001). Conclusion: Therefore, Dohsa Psycho-Rehabilitation Method (Dohsa-Hou) can be suggested as an effective method to improve interpersonal and social relationships in children with autism. Dohsa-hou method is strongly recommended as a complementary intervention for promoting adaptive, communicative, and emotional functioning in children with ASD, particularly when integrated within broader behavioral or educational plans. The intentional focus on bodily self-regulation in Dohsa-hou not only mitigates repetitive and hyperactive behaviors but also lays the groundwork for improved adaptive functioning and social engagement in children with ASD, thereby holding promising implications for both clinical practice and community-based interventions.